PENGARUH PEMBOBOTAN DAN JENIS PENILAI TERHADAP FUNGSI INFORMASI TES PERFORMANSI - S, Wakhinuddin (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2012)
Tujuan penelitian adalah untuk mengetahui pengaruh skala penilaian dengan pembobotan (SPPP), tanpa pembobotan (SPTP), penilai internal dan eksternal terhadap fungsi informasi tes performansi. Penelitian dilakukan dengan pendekatan eksperimen pada tujuh SMK di Sumatera Barat; melibatkan sampel 864 subjek dan 46 performansi. Pengambilan sampel dengan metode random sampel sederhana, penempatan subjek dengan metode random matriks sampel. Data dikumpulkan dengan tes performansi dan dianalisis dengan metode Rasch. Analisis data penelitian menggunakan Anava (desain faktorial 2x2). Hasil penelitian menunjukkan bahwa: 1) Fungsi informasi tes SPPP lebih tinggi daripada fungsi informasi tes SPTP; 2) Fungsi informasi tes oleh penilai eksternal lebih tinggi daripada fungsi informasi tes oleh penilai internal; 3) Faktor interaksi antara ragam tes performansi dan kelompok penilai mempengaruhi fungsi informasi tes.Kata kunci: tes performansi, fungsi informasi tes, skala penilaian dengan pembobotan, skala penilaian tanpa pembobotan, penilai internal dan penilai eksternal______________________________________________________________THE INFLUENCE OF PERFORMANCE TESTS WITH WEIGHTING AND ASSESSOR TYPE ON INFORMATION FUNCTION OF PERFORMANCE TESTAbstract The objective of this research was to investigate the influence of weighted and unweighted rating scales, and internal and external assessors on information function of performance test. The study was conducted on the even semester of 2004 at seven vocational schools in West Sumatera, involving 864 students and 46 performances. The sample was drawn by using simple random sampling technique, and placement was done by means of random matrix method. Factorial 2x2 design was adopted in this study. Data were collected through a performance test, and analyzed by using Rasch and two-way analysis of variance. The results of the research are: (1) the information function of the weighted rating scale test was more effective than the unweighted rating scale test, (2) the information function of the student's test assessed by external assessors was higher than that assessed by internal assessors, (3) The interaction factor between types of performance test (weighted and unweighted) and assessor groups (internal and external) affected the information function of test, (4) the information function of unweighted rating scale used by internal assessors was higher than that used by external assessors, (5) the information function of unweighted rating scale used by internal assessors was higher than the information function of weighted rating scale used by internal assessors, (6) the information function of weighted rating scale used by external assessors was higher than that of weighted rating scale used by internal assessors, (7) the information function of weighted rating scale used by external assessors was higher than that of unweighted rating scale used by internal assessors.Keywords: Performance test, informations function, weighted rating scale, unweighted rating scale, internal assessor and eksternal assessor